Pengelolaan Keuangan melalui Pengetahuan Keuangan, Sikap Keuangan, dan Gaya Hidup - Safitri, Anni; Amaniyah, Evaliati (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The purpose of this study was to determine the influence of financial knowledge, financial attitudes and lifestyle on financial management among unmarried workers in Bojonegoro Regency. The selected population is all unmarried workers in Bojonegoro Regency. Samples are selected using the purposive sampling method and 96 respondents were selected. The type of study is quantitative. The data used in the study was obtained by distributing questionnaires. Data analysis techniques consist of descriptive statistics, testing research instrument requirements, classical assumption testing, multiple linear regression analysis, and hypothesis testing using SPSS 26 tools. The result of this study show that (1) Knowledge variables and lifestyle variables partially has an effect on financial management among unmarried workers in Bojonegoro Regency (2) The financial attitude variable partially has no effect on financial management among unmarried workers in Bojonegoro Regency (3) The variables of financial knowledge, financial attitude and lifestyle simultaneously have an effect on financial management